A notoriedade dada aos atiradores na imprensa: um estudo do massacre de Suzano na reportagem da revista Veja - Carvalho, Patrícia Fossatti de (2020)
The research aims to analyze how the journalistic production of the Suzano Massacre took place in the magazine printed See, in 2019, through news values ​​and news framing. The methodology used, relates to the studies by Nivea Bona (2017), on the selection criteria, with emphasis on the news value of death, and content construction. The attack is seen as an agenda that brings together a large part of news values, being more likely to be featured in news coverage. Still, it seeks to understand how there was the framing carried out by the magazine, raising the hypothesis of the emphasis given to snipers in the news construction process (notoriety).